"Augmenting the referral pathway for retinal services among diabetic patients at Reiyukai Eiko Masunaga Eye Hospital, Nepal: a non-randomized, pre-post intervention study" - Ruchi Shrestha; Prerana Singh; Parami Dhakwa; Shailaja Tetali; Tripura Batchu; Pragati Shrestha Thapa; Varun Agiwal; Hira Pant (BMC, 2023)
Abstract Background Diabetic Retinopathy (DR) is an important public health issue in Nepal. Despite the availability of retinal services, people may not access them because of the lack of knowledge about DR and poor referral systems. DR screening uptake was low at Reiyukai Eiko Masunaga Eye Hospital(REMEH) since retina services were started. Scheer Memorial Hospital is a multispeciality hospital near to REMEH. It has no eye department but has been running a regular diabetic clinic. This was a site for referring diabetic patients for DR screening. Improving DR awareness among general physicians has the potential to address these challenges. Methods The aim of our study was to investigate the effectiveness of providing health education to selected health personnel and establish a referral pathway on the attendance of diabetic patients for retinal screening at REMEH. This was a non-randomized, pre-post intervention study design. Total of three health education sessions were provided to the health care professionals of Scheer on diabetic retinopathy using Power Point presentations, posters, pamphlets and videos. The study period was 16 months (2020 June -2021 September) and divided into 8 months pre-intervention(baseline data collection) and 8 months post intervention period. The proportional increase in number of diabetes attendance pre and post intervention was calculated by Z test. The change in knowledge of health care personnels pre and post intervention was scored and evaluated through a questionnaire and calculated by paired- t test. Data was analyzed using Excel and Epi Info 7.The Protocol was published on August 21, 2021, in JMIR Publications. Results The proportional increase in number of referrals of diabetes attendance post intervention increased from 50 to 95% and was statistically significant (p < 0.001, 95% CI: 0.214-0.688). The mean score of knowledge gained by physicians on DR awareness was more at post intervention (8.8 ± 1.32) than pre intervention (6.4 ± 1.51). It was statistically significant (p < 0.001). Conclusion This study shows that a well-planned health education intervention changes the knowledge in physicians about DR. There is an increase in the number of referrals and attendance of patients for DR screening with the change in knowledge and referral mechanism. Trial Registration Clinical Trials.gov NCT04829084; https://clinicaltrials.gov/ct2/show/NCT04829084 :02/04/2021.